Betahan as an agent of change in the lives of the dulangan manobo in sitio Mantil, Kulaman, Sultan Kudarat - Duero, Sieglyn G.
This is a descriptive study exploring the changes that has been brought about by the introduction of the betahan in the lives of the Dulangan Manobo in Sitio Mantil, Kulaman, Sultan Kudarat. The perceived and observed changes were followed by interviews. In particular, the study focuses on the influences brought about by the introduction of the betahan. The betahan was introduced in the Sitio by a migrant who had the means to own such form of technology. Despite the geographical location of Sitio Mantil the betahan has been operational for sometime now. With the introduction of the betahan two opposing views emerged among the Dulangan Manobo, that of the older generation and that of the younger generation. The elders refused to patronized the betahan since it is not part of their culture and they did not wish to embrace the changes the betahan brought to their community. On the other hand, youth instantly accepted the betahan because it served as a medium for learning which altered their indigenous way of living. The changes that occurred among the Dulangan Manobo in Sitio Mantil can also be attributed to the fast migration of the settlers to the Sitio. The increase in the number of the settlers in the area increases the interaction between people of different cultures.
Thesis, Undergraduate (BA Social Science) -- U. P. in Mindanao